(untitled) (Clinics, 2009)
OBJECTIVE: Evaluate whether exhaled nitric oxide may serve as a marker of intraoperative bronchospasm. INTRODUCTION: Intraoperative bronchospasm remains a challenging event during anesthesia. Previous studies in asthmatic patients suggest that exhaled nitric oxide may represent a noninvasive measure of airway inflammation. METHODS: A total of 146,358 anesthesia information forms, which were received during the period from 1999 to 2004, were reviewed. Bronchospasm was registered on 863 forms. From those, three groups were identified: 9 non-asthmatic patients (Bronchospasm group), 12 asthmatics (Asthma group) and 10 subjects with no previous airway disease or symptoms (Control group). All subjects were submitted to exhaled nitric oxide measurements (parts/billion), spirometry and the induced sputum test. The data was compared by ANOVA followed by the Tukey test and Kruskal-Wallis followed by Dunn's test. RESULTS: The normal lung function test results for the Bronchospasm group were different from those of the asthma group (p